In vivo skin fluorescence imaging in young Caucasian adults with early malignant melanomas - Piérard GE; Hermanns-Lê T; Piérard SL; Dewalque L; Charlier C; Piérard-Franchimont C; Delvenne P (Dove Medical Press, 2014)
Gérald E Piérard,1 Trinh Hermanns-Lê,2 Sébastien L Piérard,3 Lucas Dewalque,4 Corinne Charlier,4 Claudine Piérard-Franchimont,2 Philippe Delvenne2 1Laboratory of Skin Bioengineering and Imaging (LABIC), Department of Clinical Sciences, Liège University, 2Department of Dermatopathology, Unilab Lg, University Hospital of Liège, 3INTELSIG Laboratory, Montefiore Institute, University of Liège, 4Department of Clinical, Forensic and Environmental Toxicology, University Hospital of Liège, Liège, Belgium Background: Human cutaneous malignant melanoma (CMM) is an aggressive cancer showing a dramatic worldwide increase in incidence over the past few decades. The most prominent relative epidemiological increase has been disclosed in young women. The aim of the study was to assess the effects of chronic sun exposures in order to rate the extend of melanocytic stimulations in the vicinity of CMM. Methods: The study was designed to evaluate the melanin distribution and density using ultraviolet light illumination. The present study was performed on surgical excision specimens of thin CMM lesion removed from the upper limbs of 55 Caucasian adults (37 women and 18 men). Two control groups comprised 23 men and 21 women of similar ages who had medium-size congenital melanocytic nevi, also present on the upper limbs. The peritumoral skin was scrutinized using a Visioscan® VC98 device, revealing the faint mosaic melanoderma (FMM) pattern that grossly indicates early signs of chronic photodamage in epidermal melanin units. Results: The median extent of relative FMM was significantly higher in the CMM male group. By contrast, the CMM female group showed a reverse bimodal distribution in FMM size. Only 12/37 (32.5%) of the CMM female group had an increased FMM size, whereas 25/37 (67.5%) of females with CMM had a global FMM extent in the normal range, relative to the controls. Conclusion: Thin CMM supervening in young women appear unrelated to repeat photoexposure. Other mechanisms are possibly involved. Keywords: gender, HOX gene, ULEV method, genotoxicity, faint mosaic melanoderma